Perubahan Budaya Tatap Muka Menjadi Online dalam Bimbingan Skripsi Mahasiswa - Iswanto Iswanto; Dasrun Hidayat (LUGAS Jurnal Komunikasi, 2020)
Face-to-face communication has turned directly online, which encourages changes in the communication culture of lecturers. Changes in the communication culture require communication competence so that face-to-face thesis guidance runs effectively. Therefore, this research aims to measure the communication competence of lecturers and students when carrying out online guidance. To answer the research objectives, researchers used a case study with a qualitative approach. The theory of analysis used in this study uses the theory of communicative competence based on two dimensions: the cognitive dimension and the behavioral dimension. The data technique used in this study used purposive sampling, which includes several criteria for informants, including two final-year students preparing a thesis using the zoom cloud meeting application, then actively carrying out online thesis guidance and other supporting informants of two supervisors. The results showed that the face-to-face change to online in the guidance of the online thesis culture is still positive because there are communication competencies that are owned; there are two components of communication in online thesis guidance, namely: knowledge (knowledge) and skills (skills), the most positive communication competence—perceived by students and lecturers, namely skills.